EFEKTIFITAS PEMANFAATAN LINGKUNGAN SEKOLAH DALAM MENINGKATKAN KEMAMPUAN MEMBACA KATA BAGI ANAK TUNAGRAHITA RINGAN - Marwan - Toni (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstract : This research was motivated by the presence of a mild mental retardation children who have difficulty reading words in SLB N 1 Padang. The purpose of this study so that children are able to read words with the utilization of the school environment. The school environment is an environment that many affect both attitudes and learning styles of children. Therefore, researchers are interested in appealing this matter so that the child is able to read the words properly so that the learning process can be run well.